2019
DOI: 10.1111/jeb.13547
|View full text |Cite
|
Sign up to set email alerts
|

Does operational sex ratio influence relative strength of purging selection in males versus females?

Abstract: According to theory, sexual selection in males may efficiently purge mutation load of sexual populations, reducing or fully compensating 'the cost of males'. For this to occur, mutations not only need to be deleterious to both sexes, they also must affect males more than females. A frequently overlooked problem is that relative strength of selection on males versus females may vary between environments, with social conditions being particularly likely to affect selection in males and females differently. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Mutational load has greater potential to be purged via selection in males, owing to sexual selection operating more strongly in males, particularly where condition‐dependent selection is strong (Grieshop et al, 2021; Rowe & Houle, 1997; Whitlock & Agrawal, 2009). However, the relative strength of purging selection in males versus females might vary depending on environmental conditions (Plesnar‐Bielak et al, 2020). Moreover, experimental evidence has shown only limited effects of purging on fitness restoration and its efficiency may depend on the nature of genetic variance (Frankham, 2015; Wright et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Mutational load has greater potential to be purged via selection in males, owing to sexual selection operating more strongly in males, particularly where condition‐dependent selection is strong (Grieshop et al, 2021; Rowe & Houle, 1997; Whitlock & Agrawal, 2009). However, the relative strength of purging selection in males versus females might vary depending on environmental conditions (Plesnar‐Bielak et al, 2020). Moreover, experimental evidence has shown only limited effects of purging on fitness restoration and its efficiency may depend on the nature of genetic variance (Frankham, 2015; Wright et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, considerable empirical work has tested whether sexual selection in males can indeed increase selection against deleterious mutations and thereby aid population persistence (Cally et al, 2019; Rowe & Rundle, 2021). Results are mixed: some experimental studies on a variety of species, for example, the fruit fly Drosophila melanogaster or the bulb mite Rhizoglyphus robini , report positive effects of sexual selection on population fitness (Almbro & Simmons, 2014; Godwin et al, 2020; Grieshop et al, 2016; Hollis et al, 2009; Jarzebowska & Radwan, 2010; Lumley et al, 2015; Parrett et al, 2022; Radwan, 2004), while other studies in the same or similar species did not find such effects (Allen et al, 2017; Arbuthnott & Rundle, 2012; Chenoweth et al, 2015; Hollis & Houle, 2011; Plesnar‐Bielak et al, 2011, 2020; Prokop et al, 2019). Meanwhile, studies of wild populations have mostly found negative effects of sexual selection on population persistence (Bro‐Jørgensen, 2014; Doherty et al, 2003; Martins et al, 2018; McLain et al, 1995; McLain & Vives, 1998; Morrow & Pitcher, 2003), but some studies report no effect (Morrow & Fricke, 2004; Prinzing et al, 2002) or positive effects (Parrett et al, 2019).…”
Section: Introductionmentioning
confidence: 96%